KEHIDUPAN ANAK NELAYAN DALAM KARYA SENI GRAFIS - Novendra, Yofita Sandra, S.Pd., M.Pd. Drs. Irwan, M.Sn. (Serupa The Journal of Art Education, 2018)
The creation of this final work aims how to visualize the reality of fisherman's child in the coastal areas. Fishermen child couldn’t enjoy education still have not gotten the right right when past the period where they should be ditahap education. The methods and work processes used in the creation of this graphic art work through several stages: preparation, elaboration, synthesis, concept realization, finishing. From this graphic artwork it can be concluded that there are still many fishermen who do not go to school because they help their parents to earn a living. The title of the work is in the lift "Small Fishermen, Waiting Father, Children Twilight, Gathering, Ports, Net of Life, Seaside, Selling Catch, Father and Mother and Back Home".Keywords: Fishermen’ child, graphic arts, serigraphy